Maqashid Shariah Study on The Recording of Unregistered Marriage in The Family Card - Nazar Fuadi Nur; Azhari Yahya; Efendi Idris (Jurnal Penelitian Hukum De Jure, 2022)
This study aims to analyzes the status of unregistered marriages recorded in the Family Card from maqashid syariah point of view. The methods applied in this study is normative legal research by relying on secondary data. The approaches used to analyze research problem are statutory and conceptual approach. The results of study indicate that according to Islamic law point of view unregistered marriage is a legal marriage. Marriage and marriage registration are two different dimensions. The marriage contract which is pledged based on syariah law results in religious legal relationship; while marriage registration results in legal acknowledgement in the view of national law and may protect   the couple from any legal issue that may arise in the future. From the perspective of maqashid syariah, unregistered marriage may cause a lot of harm for the lives of couple and their children. The status of unregistered marriage is hard to be recognized by the Religious Courts because there is no evidence of marriage that may be shown by the couple. Therefore, it is suggested for unregistered marriage couple to conduct isbat nikah (renew of marriage) so that their marriage is recognized and registered by the state through Office of Religious Affairs.